Distal Iliotibial Band Z-lengthening for Iliotibial Band Syndrome - Scott E. Dart MD; Zane Hyde MD; Winston Gwathmey MD; Brian C. Werner MD (Video Journal of Sports Medicine, 2021)
Background: This technique video reviews an iliotibial band Z-lengthening procedure for iliotibial band (ITB) syndrome using a patient case example. Indications: Indications for considering surgical intervention include a diagnosis of iliotibial band syndrome, ruling out other possible etiologies of knee pain, and a minimum of 6 months of failed conservative treatment. Technique Description: There are several surgical techniques described in the literature, although the ITB Z-lengthening procedure is preferred at our institution. This technique uses a “Z”-type incision through the distal ITB to allow lengthening of the ITB and to allow access for surgical debridement of the underlying inflamed bursa. Nonabsorbable suture is then used for a side-to-side repair of the ITB in the elongated position. Results: Complications from this technique are uncommon, and the few published outcomes from this procedure show good clinical results and return to preactivity levels. Discussion/Conclusion: Preoperative planning should include analysis of lower extremity alignment and can include advanced imaging to rule out intra-articular pathology. Diagnostic arthroscopy is typically used at the start of the case for completeness. Distal iliotibial band Z-lenghtening can be a successful surgical option for patients who have failed extensive conservative treatment for iliotibial band syndrome.